2007
DOI: 10.1055/s-2007-966056
|View full text |Cite
|
Sign up to set email alerts
|

Indium(III) Chloride/Water: A Versatile Catalytic System for the Synthesis of C-Furyl Glycosides and Trihydroxyalkyl Furan Derivatives

Abstract: I n d i u m ( I I I ) C h l o r i d e / Wa t e r : A V e r s a t i l e C a t a l y t i c S y s t e m JhilluAbstract: Hexose sugars undergo smooth coupling with 1,3-diketones and b-keto esters in the presence of 10 mol% of indium(III) chloride in water at 80 °C to furnish C-furyl glycosides in excellent yields, whereas pentose sugars produce trihydroxyalkyl-substituted furan derivatives with high selectivity. The reactions of cyclic ketones such as cyclohexane-1,3-dione or dimedone with D-glucose in acetonitril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…This paper presents the analysis of products obtained from the mild base‐catalyzed condensation of cyclic β ‐diketones with representative isotopically labeled aldose sugars. The reaction products and their peracetylated analogs conform to the expected structures 1 and 2 (Scheme ) and there is no evidence of previously reported ketofurans that are obtained with Lewis acid catalysts 9–13. The EI‐generated ion fragmentation pathways deduced from the analysis are presented and discussed with respect to our earlier work 2…”
Section: Methodsmentioning
confidence: 65%
“…This paper presents the analysis of products obtained from the mild base‐catalyzed condensation of cyclic β ‐diketones with representative isotopically labeled aldose sugars. The reaction products and their peracetylated analogs conform to the expected structures 1 and 2 (Scheme ) and there is no evidence of previously reported ketofurans that are obtained with Lewis acid catalysts 9–13. The EI‐generated ion fragmentation pathways deduced from the analysis are presented and discussed with respect to our earlier work 2…”
Section: Methodsmentioning
confidence: 65%
“…Aer a set of optimizations, it was found that the use of 1.0 equiv. of sodium methoxide furnished an excellent yield (75%) of the desired product (7) in 12 h. Therefore, compound 4 was allowed to condense with a series of aromatic aldehydes in the presence of sodium methoxide in methanol to give C-glycosylated cinnamoyl furan derivatives (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) in excellent yield. The formation of the trans-cinnamoyl double bonds (E-isomers) in the molecules was conrmed from a 1 H NMR spectral analysis [doublets with large coupling constant (J ¼ 15.5-16.0 Hz)].…”
Section: Resultsmentioning
confidence: 99%
“…The C-glycosylated furan derivatives containing an a-methylcarbonyl functionality were prepared from commercially available reducing sugars under aqueous reaction conditions, following an earlier report. 23,24 The furan derivatives were treated with a number of aryl aldehydes in the presence of a base to furnish the desired compounds. Some selected Ccinnamoylated products were acetylated to check whether the O-acetyl group has any inuence on the biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…Direct use of unprotected sugar lactols for coupling with C -nucleophiles represents an attractive approach en route to C -glycosides. Henry condensation of glucose 566 with nitromethane under the catalysis of sodium methoxide followed by reflux in water to promote dehydration and cyclization afforded β- C -glucoside 567 in 53% yield (Scheme ). Coupling of glucose 566 with pentane-2,4-dione 568 in the presence of sodium bicarbonate proceeded through Knoevenagel reaction and intramolecular Michael cyclization to give β- C -glucoside 569 in excellent yield. ,, Reactions of other types of unprotected sugar lactols such as 2-acetamido sugars, heptoses, xylose, and galactose with C -nucleophiles such as 1,3-dicarbonyl compounds and 1,3-oxazine-2-thiones in the presence of base (NaHCO 3 , Na 2 CO 3 , NaH, or KOH) or Lewis acid (InCl 3 , CoCl 2 ) also afforded the corresponding C -pyrano- or C -furanoglycosides in good yields with high β-stereoselectivities. ,− As an example of Sc­(OTf) 3 -promoted C -glycosylation of unprotected sugar lactols with aryl compounds, direct glycosylation of glucose 566 with 570 gave β- C -aryl glycoside 571 (65%). Horner–Wadsworth–Emmons reaction of lactose 572 with β-ketophosphonate 573 under basic conditions provided β- C -glucoside 574 (67%). , Aldol reaction of d -deoxyribose 575 with acetoacetic ester 576 catalyzed by i Pr 2 NEt and 2-pyridone led to hemiketal 577 with high diastereoselectivity (45%, dr > 49:1) . Under the promotion of l -proline and DBU, the Knoevenagel–Michael cascade reaction of d -ribose 578 with dimethyl 3-oxoglutarate 579 gave C -glycoside 580 (86%, dr > 49:1), whereas the aldol-Michael reaction of 578 with acetone 581 provided a mixture of α- and β- C -glycosides 582 and 583 and the hemiketal 584 in a 69% overall yield. Other amine-mediated aldol-Michael reactions of unprotected ketoses or 2- N -acyl-aldohexoses with acetone 581 have also been reported for the synthesis of C -glycosides. , Recently, Cu­(I)-catalyzed dehydrative C -glycosylation of unprotected 2-deoxy sugar 585 with acetophenone 586 in the presence of diphosphine ligand L1 was reported to give C -glycosi...…”
Section: C-glycosylation With Sugar Lactolsmentioning
confidence: 99%